RLC 171 (Varsha Alsi 2), the most recent and promising linseed variety for Rainfed condition of Himanchal Pradesh, Jammu and Kashmir, Punjab, Jharkhand, Uttar Pradesh, Assam, Bihar and Nagaland: RLC 171 (Varsha Alsi 2), the most recent and promising linseed variety for Rainfed condition of Himanchal Pradesh, Jammu and Kashmir, Punjab, Jharkhand, Uttar Pradesh, Assam, Bihar and Nagaland - NANDAN MEHTA; K P VERMA; SANJAY K DWIWEDI; B P KATLAM; SONAL UPADHYAY (Journal of Oilseeds Research, 2023)
Linseed (Linum usitatissimum L.) 2n = 30, belongs to the genus Linum of the family Linaceae, Which is a self pollinated crop. India ranks third in area under linseed followed by Canada, China whereas, in production it stands fifth.